Cell cycle regulation for meiosis in mammalian germ cells - Ryuki SHIMADA; Kei-ichiro ISHIGURO (The Society for Reproduction and Development, 2023)
In mouse fetal gonads, germ cell development is accompanied by changes in cell cycle mode in response to external signals and intrinsic mechanisms of cells. During fetal development, male germ cells undergo G0/G1 arrest, while female germ cells exit the mitotic cell cycle and enter meiosis. In fetal testes, NANOS2 and CYP26B1 force germ cells to stay in G0/G1 arrest phase, preventing them from entering the meiotic cell cycle. In the fetal ovary, external signals, such as RA, BMP, and WNT, promote the competency of female germ cells to enter the meiotic cell cycle. MEIOSIN and STRA8 ensure the establishment of the meiotic cell cycle by activating meiotic genes, such that meiotic entry coincides with the S phase. This review discusses germ cell development from the viewpoint of cell cycle regulation and highlights the mechanism of the entry of germ cells into meiosis.